Three-dimensional solid-state lithium battery and preparation method thereof
By using alkenyl ionic liquid polymers in three-dimensional solid lithium batteries to construct solid electrolytes and combining solid fillers, the problem of insufficient cyclability of the battery at different temperatures is solved, and high specific capacity and excellent cycling performance are achieved.
Patent Information
- Application Number
- CN202510111644.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing three-dimensional solid-state lithium batteries have insufficient cyclicity at different temperatures, especially in high and low temperatures, which is difficult to meet the current demand.
The solid electrolyte is constructed with alkenyl ion-containing liquid polymers, and combined with solid fillers, improve the contact between the electrode and the solid electrolyte, enhance the effective transmission of ions, block the growth of lithium "dendrites", and stabilize the deposition of lithium metal.
The high specific capacity and excellent cycling performance of three-dimensional solid-state lithium batteries are achieved, especially the stability of the high and low temperatures is significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a three-dimensional solid-state lithium battery and a preparation method thereof. Background Art
[0002] 3D Solid-State Lithium Battery is a new type of lithium battery. Its core technology is to use solid electrolyte instead of traditional liquid electrolyte, and to achieve three-dimensional design in the battery structure. Compared with traditional lithium batteries, 3D solid-state lithium batteries have significant advantages in energy density, safety and service life. Solid-state lithium batteries are safer than traditional liquid electrolyte batteries because they use solid electrolytes. Applying 3D solid-state lithium batteries to the toy field is safer than traditional batteries.
[0003] The solid-solid interface in existing solid-state lithium batteries brings huge interface resistance, which affects the rate performance and material capacity, and the current surfactant improvement effect is not obvious enough, resulting in the difficulty in solving the interface difference problem. The composite positive electrode of the lithium battery in the Chinese invention patent publication CN113629221A is composed of a porous positive electrode skeleton and a filled polymer electrolyte. The rate performance and cycle stability of the solid-state lithium battery are improved, and the utilization rate and high voltage tolerance of the electrode material are enhanced, but it cannot improve the cyclability of the lithium battery at different temperatures; the multilayer structure lithium metal electrode in the Chinese invention patent publication CN106716690A can protect the reactivity of the lithium metal from damage by moisture or the battery environment, and prevent the formation of dendrites. In addition, the formation of the buffer layer prevents the deterioration of ion conductivity caused by the oxide layer formed on the lithium metal plate during the formation of the protective layer, but the residual electronic conductivity of its solid electrolyte will cause the electrons in the metallic lithium negative electrode to move toward the electric field; the Chinese invention patent publication text CN108695558A discloses an all-solid-state battery core and a high-performance solid-state battery containing the battery core, which significantly improves the safety and cycle life of the battery, reduces the interface impedance, and improves the long-term use integrity and energy density of the battery. However, in fact, the preparation of the lithium battery has poor cyclability at high temperature and is difficult to meet the current needs.
[0004] Therefore, there is an urgent need for a three-dimensional solid-state lithium battery having high specific capacity and cyclic high-temperature and cyclic low-temperature stability. Summary of the invention
[0005] The object of the present invention is to provide a three-dimensional solid-state lithium battery and a preparation method thereof, wherein the three-dimensional solid-state lithium battery has high specific capacity and excellent cyclability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: In the first aspect, the present invention provides a three-dimensional solid-state lithium battery, comprising a positive electrode sheet, a negative electrode sheet, and a solid electrolyte; the positive electrode sheet comprises a three-dimensional foam porous aluminum foil and a positive electrode active material and a positive electrode conductive agent coated on the surface of the three-dimensional foam porous aluminum foil; the negative electrode sheet comprises a three-dimensional foam porous copper foil and a negative electrode active material and a negative electrode conductive agent coated on the surface of the three-dimensional foam porous copper foil; the solid electrolyte comprises a polymer, a lithium salt, and a solid filler; wherein the polymer contains a structural unit A from an olefinic ionic liquid and a structural unit B from 2-hydroxyethyl acrylate.
[0007] In the present invention, a polymer obtained by polymerization of an olefin-containing ionic liquid is used to construct a solid electrolyte, and a solid filler is used at the same time. The coordinated effect of the two can promote the contact between the electrode and the solid electrolyte, better increase the effective transmission of ions during the cycle, effectively block the growth of lithium "dendrites", and effectively stabilize the deposition of lithium metal during the cycle, so that the solid-state lithium battery has a higher specific capacity and excellent cycle performance.
[0008] The polymer in the present invention contains a structural unit A derived from an alkenyl ionic liquid, which means that the polymer is obtained by polymerization of a monomer containing an alkenyl ionic liquid. Preferably, the alkenyl ionic liquid is selected from at least one of 1-allyl-3-methylimidazolium hexafluorophosphate, 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methylimidazolium trifluoromethanesulfonate, 1-allyl-3-ethylimidazolium hexafluorophosphate and 1-allyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide, preferably 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and / or 1-allyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide. In the present invention, it is found that using the above-mentioned preferred ionic liquid as a polymerization monomer can not only better improve the specific capacity of the battery, but also better improve the thermal stability of the battery. This may be because the polymer formed by the above-mentioned monomers has an imidazole-trifluoromethanesulfonyl structure, which can improve the thermal stability of the solid electrolyte and has better stability and compatibility with the lithium metal negative electrode.
[0009] Preferably, the mass ratio of the structural unit B to the structural unit A is 1:(0.1-1), for example, 1:0.1, 1:0.1, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, preferably 1:(0.3-0.4).
[0010] The contents of the structural unit B and the structural unit A in the present invention are both calculated based on the weight of their corresponding monomers.
[0011] In the present invention, lithium salt refers to a salt compound formed by lithium element and other elements. Preferably, the lithium salt is selected from at least one of lithium oxalate borate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate and lithium difluorooxalate borate, preferably lithium bis(trifluoromethylsulfonyl imide) and / or lithium bis(fluorosulfonyl imide).
[0012] The use of solid fillers in the present invention can better increase the specific capacity and cold resistance of lithium batteries. It is speculated that this may be because the solid fillers have a pore structure that can better provide continuous lithium ion transmission channels, and lithium ions can be conducted through polymers and polymer two-phase interfaces, thereby better improving the utilization of positive and negative electrode active materials. The cross-linking interaction between inorganic fillers and polymers can improve the stability of the electrolyte, thereby making the lithium battery have better stability.
[0013] Preferably, the solid filler is selected from molecular sieves modified with vinyl coupling agents.
[0014] In the present invention, experimental studies have found that although the use of general solid fillers can increase the specific capacity of lithium batteries to a certain extent, it will affect the recycling performance of lithium batteries. This may be because the high energy and instability of the surface of general solid fillers will cause nanoparticles to agglomerate, which will affect the transmission of lithium ions when used in lithium batteries during the cycle process. Studies have found that the use of vinyl coupling agent-modified molecular sieves can not only better increase the specific capacity of lithium batteries, but also better increase the stability of lithium batteries, especially low-temperature stability. It is speculated that this is because the vinyl coupling agent-modified molecular sieve can produce cross-linking with the polymer, so that it has better mechanical properties at low temperatures, which is more conducive to efficient and stable ion transmission at the solid electrolyte-electrode interface.
[0015] Preferably, the preparation method of the vinyl coupling agent modified molecular sieve comprises: mixing water and molecular sieve, adjusting the pH value of the system to 9-10 with ammonia water, then adding vinyl coupling agent for reaction, filtering, and solid phase drying to obtain the vinyl coupling agent modified molecular sieve.
[0016] Preferably, when preparing the vinyl coupling agent modified molecular sieve, the molecular sieve is selected from ZSM-5 molecular sieve.
[0017] In the present invention, the use of ZSM-5 molecular sieve can better increase the specific capacity of the lithium battery, presumably because the special three-dimensional pore structure of the ZSM-5 molecular sieve is more conducive to the transmission of lithium ions.
[0018] Preferably, the average particle size of the ZSM-5 molecular sieve is 20-200 nm, preferably 80-150 nm.
[0019] Preferably, the silicon-aluminum molar ratio of the ZSM-5 molecular sieve is 80-100.
[0020] The ZSM-5 molecular sieve in the present invention can be obtained commercially, for example, from Shandong Hefa Environmental Protection Technology Co., Ltd.
[0021] In the present invention, ammonia water is a solution of ammonia gas dissolved in water, and its volume concentration is generally 10%-30%.
[0022] Preferably, the vinyl coupling agent is selected from at least one of coupling agent A-171, coupling agent A-151 and coupling agent A-172, preferably coupling agent A-171.
[0023] Preferably, when preparing the vinyl coupling agent modified molecular sieve, the mass ratio of water to molecular sieve is 1:(0.3-0.8), preferably 1:(0.4-0.5).
[0024] Preferably, when preparing the vinyl coupling agent modified molecular sieve, the mass ratio of the vinyl coupling agent to the molecular sieve is 1:(1.2-2), preferably 1:(1.5-1.6).
[0025] In the present invention, when preparing the vinyl coupling agent modified molecular sieve, the mixing conditions are not particularly limited and can be conventional mixing in the art, as long as the water and the molecular sieve can be mixed uniformly.
[0026] Preferably, when preparing the vinyl coupling agent modified molecular sieve, the reaction conditions include: temperature of 40-50° C. and reaction time of 1-2 hours.
[0027] In the present invention, when preparing the vinyl coupling agent modified molecular sieve, the drying conditions are not particularly limited. Preferably, the solid phase drying conditions include: a temperature of 100-120° C. and a time of 8-24 h.
[0028] Preferably, the lithium salt is calculated as lithium element, and the mass ratio of the structural unit B, the structural unit A, the lithium salt and the solid filler is 1: (0.3-0.4): (0.003-0.005): (0.06-0.07).
[0029] Preferably, the solid electrolyte is obtained by in-situ polymerization of 2-hydroxyethyl acrylate, alkenyl ionic liquid, lithium salt and solid filler.
[0030] In the present invention, the three-dimensional foam porous aluminum foil is a conventional material in the art. Preferably, the three-dimensional foam porous aluminum foil has a thickness of 1-2 mm, a pore size of 4-6 mm, and a porosity of 40%-60%. It can be obtained commercially, for example, from Foshan Zhongji Xinmi New Materials Co., Ltd.
[0031] Preferably, the positive electrode active material is selected from at least one of CM811, NCM622, NCM523 and NCM111.
[0032] The positive electrode conductive agent is selected from at least one of conductive carbon black, acetylene black, graphene, carbon nanotubes, conductive graphite and carbon fiber, preferably conductive carbon black.
[0033] Preferably, the average particle size of the conductive carbon black is 30-50 mm.
[0034] The conductive carbon black in the present invention can be obtained from the market, for example, its model is Super-P-Li (SP).
[0035] Preferably, the mass ratio of the positive electrode active material to the positive electrode conductive agent is 100:(3-4).
[0036] In the present invention, the three-dimensional foam porous copper foil is a conventional material in the art. Preferably, the three-dimensional foam porous copper foil has a thickness of 1-2 mm, a pore size of 4-6 mm, and a porosity of 40%-60%. The shell is commercially available, for example, from Foshan Zhongji Enmi New Materials Co., Ltd.
[0037] Preferably, the negative electrode active material is selected from lithium titanium oxide (Li4Ti5O12).
[0038] Preferably, the negative electrode conductive agent is selected from at least one of conductive carbon black, graphene and carbon nanotubes, preferably conductive carbon black.
[0039] Preferably, the average particle size of the conductive carbon black is 30-50 mm.
[0040] The conductive carbon black in the present invention can be obtained from the market, for example, its model is Super-P-Li (SP)
[0041] Preferably, the mass ratio of the negative electrode active material to the negative electrode conductive agent is 100:(2-3).
[0042] In a second aspect, the present invention provides a method for preparing the three-dimensional solid-state lithium battery according to the first aspect of the present invention, the preparation method comprising: S1 Preparation of positive electrode sheet: The positive electrode active material, positive electrode conductive agent and positive electrode binder are first mixed, and then N-methylpyrrolidone is added according to the solid content of 50-65wt% to continue the second mixing to obtain positive electrode slurry, and then the positive electrode slurry is coated on the three-dimensional foam porous aluminum foil through a coating machine and oven drying, and finally the positive electrode is punched to obtain the positive electrode sheet; S2 Preparation of negative electrode sheet: A negative electrode active material, a negative electrode conductive agent and a negative electrode binder are mixed, and then N-methylpyrrolidone is added according to a solid content of 50-65wt% and mixed to obtain a negative electrode slurry. The negative electrode slurry is then coated on a three-dimensional foam porous copper foil and dried in a coating machine and oven. Finally, a negative electrode sheet is punched to obtain a negative electrode sheet. S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt are mixed for a third time, a solid filler is added and mixed for 10-30 minutes, and then an initiator is added and mixed for 5-10 minutes to obtain a solid electrolyte precursor, the solid electrolyte precursor is cast on a porous rigid support material to initiate polymerization, and finally punching is performed; S4 Assembly of three-dimensional solid-state lithium battery: attach the positive electrode sheet in step S1 to one side of the diaphragm with solid electrolyte attached, attach the negative electrode sheet in step S2 to the other side of the diaphragm with solid electrolyte attached, and then perform a first pressing to obtain a battery cell, and then place the battery cell into a shell for a second pressing to obtain a three-dimensional solid-state lithium battery.
[0043] In step S1, there is no special limitation on the conditions of the first mixing, and mixing is generally performed at room temperature for 5-10 minutes; there is no special limitation on the time of the second mixing, and mixing is performed evenly, and mixing is generally continued for 30-40 minutes.
[0044] In step S1, generally 40-60 mg / cm 2 Areal density weight for coating.
[0045] In step S1, the positive electrode punching is a conventional operation method in the art, and the present invention will not elaborate on it here. For example, the positive electrode punching obtains a circular positive electrode sheet with a diameter of 8-15 mm.
[0046] Preferably, the specific steps of step S1 are as follows: preparing the positive electrode sheet: mixing the positive electrode active material, the positive electrode conductive agent and the positive electrode binder at room temperature for 5-10 minutes, then adding N-methylpyrrolidone according to the solid content of 50-65wt% and continuing to mix for 30-40 minutes to obtain a positive electrode slurry, and then mixing the positive electrode slurry according to the solid content of 40-60mg / cm 2 The surface density weight is coated on a three-dimensional foam porous aluminum foil, passed through a coating machine and dried in an oven, and finally the positive electrode is punched out to obtain a circular positive electrode sheet of 8-15 mm.
[0047] Preferably, in step S2, the conditions for mixing A are not particularly limited, and mixing is generally performed at room temperature for 5-10 minutes, and the time for mixing B is generally 30-40 minutes.
[0048] Preferably, in step S2, the negative electrode slurry is 15-20 mg / cm 2The areal density is weight coated on a three-dimensional foam porous copper foil.
[0049] In step S2, the negative electrode punching is a conventional operation method in the art, and the present invention will not elaborate on it here. For example, the negative electrode punching obtains a circular negative electrode sheet with a diameter of 8-15 mm.
[0050] Preferably, the specific steps in step S2 include: preparation of the negative electrode sheet: mixing the negative electrode active material, the negative electrode conductive agent and the negative electrode binder at room temperature for 5-10 minutes, then adding N-methylpyrrolidone according to the solid content of 50-65wt% and continuing to mix for 30-40 minutes to obtain the negative electrode slurry, and then mixing the negative electrode slurry according to the solid content of 15-20mg / cm 2 The surface density weight is coated on the three-dimensional foam porous copper foil, passed through a coating machine and oven drying, and finally the negative electrode is punched out to obtain a circular negative electrode sheet with a diameter of 8-15mm.
[0051] Preferably, in step S3, the third mixing conditions include: mixing at 30-40° C. for 10-30 min.
[0052] Preferably, in step S3, the conditions for the initiator polymerization include: initiation at 60-70°C for 1-2 hours and then polymerization at 40-50°C for 6-8 hours.
[0053] The size of the punched sheet in step S3 is selected according to the size of the positive electrode sheet in step S1 and the size of the negative electrode sheet in step S2.
[0054] Preferably, the specific steps in step S3 include: preparation of a diaphragm with a solid electrolyte attached: mixing an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt at 30-40°C for 10-30 minutes, then adding a solid filler and continuing to mix for 10-30 minutes, and then adding an initiator and mixing for 5-10 minutes to obtain a solid electrolyte precursor, casting the solid electrolyte precursor on a porous rigid support material, initiating at 60-70°C for 1-2 hours, and then polymerizing at 40-50°C for 6-8 hours, and then punching to obtain a circular diaphragm with a solid electrolyte attached and a diameter of 8-15 mm.
[0055] Preferably, in step S4, the first pressing conditions include: 60-70°C, 800-10000kg / cm 2 Heat press for 1-2 minutes. Then press at room temperature, 800-10000kg / cm 2 Cold press for 2-4 minutes.
[0056] Preferably, in step S4, the second pressing conditions include: 70-80°C, pressure 400-600kg / cm 2Heat press for 3-5 minutes, then at room temperature, 800-10000kg / cm 2 Cold press for 2-4 minutes.
[0057] More preferably, the specific steps in step S4 include: attaching the positive electrode sheet in step S1 to one side of the diaphragm with the solid electrolyte attached, attaching the negative electrode sheet in step S2 to the other side of the diaphragm with the solid electrolyte attached, and then heating at 60-70°C and 800-10000kg / cm 2 Heat press for 1-2 minutes. Then press at room temperature, 800-10000kg / cm 2 The battery cell is then placed in a housing at 70-80°C and a pressure of 400-600kg / cm 2 Heat press for 3-5 minutes, then at room temperature, 800-10000kg / cm 2 The three-dimensional solid-state lithium battery is obtained by cold pressing for 2-4 minutes.
[0058] In step S1, the mass ratio of the positive electrode active material to the positive electrode binder is 100:(3-4).
[0059] In step S1, the positive electrode binder is selected from polyvinylidene fluoride binder and / or polyacrylate binder, preferably polyvinylidene fluoride binder.
[0060] The polyvinylidene fluoride adhesive in the present invention can be obtained commercially, for example, from Dongguan Fubang Anticorrosive Materials Co., Ltd.
[0061] In step S2, the mass ratio of the negative electrode active material to the negative electrode binder is 100:(3-4).
[0062] In step S2, the negative electrode binder is selected from polyvinylidene fluoride binder and / or polyacrylate binder, preferably polyvinylidene fluoride binder.
[0063] The polyvinylidene fluoride adhesive in the present invention can be obtained commercially, for example, from Dongguan Fubang Anticorrosive Materials Co., Ltd.
[0064] Preferably, in step S3, the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:(0.5-1).
[0065] Preferably, the organic solvent is selected from at least one of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate and dimethyl carbonate.
[0066] Preferably, in step S3, the initiator is selected from at least one of dodecanoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate, preferably dodecanoyl peroxide.
[0067] Preferably, the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:(0.004-0.007).
[0068] Preferably, the porous rigid support material is selected from a non-woven fabric membrane, and preferably the thickness of the non-woven fabric membrane is 200-400 microns, which can be obtained commercially, for example, from Dongguan Kelude New Energy Technology Co., Ltd.
[0069] Preferably, the casting amount of the solid electrolyte precursor is such that the thickness of the solid electrolyte is 50-100 microns.
[0070] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The polymer in the solid electrolyte of the present invention contains structural units derived from olefinic ionic liquids, which can make the lithium battery have a high specific capacity. The high specific capacity can further improve the energy density of the solid-state lithium battery. The reason may be that the ionic liquid enables the solid electrolyte to promote the construction of the lithium ion penetration network of the positive electrode active material.
[0071] 2. The solid electrolyte in the present invention can alleviate the impedance of the interface between the positive / negative electrode material and the solid electrolyte during the charging and discharging and cycling process of the solid-state lithium battery at room temperature, low temperature and high temperature, and help improve the high-temperature and low-temperature cycling stability of the battery. DETAILED DESCRIPTION
[0072] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] Example 1 This embodiment provides a three-dimensional solid-state lithium battery, including a positive electrode sheet, a negative electrode sheet, and a solid electrolyte; the positive electrode sheet includes a three-dimensional foam porous aluminum foil and a positive electrode active material and a positive electrode conductive agent coated on the surface of the three-dimensional foam porous aluminum foil; the negative electrode sheet includes a three-dimensional foam porous copper foil and a negative electrode active material and a negative electrode conductive agent coated on the surface of the three-dimensional foam porous copper foil; the solid electrolyte includes a polymer, a lithium salt, and a solid filler; the polymer contains a structural unit A from an olefinic ionic liquid and a structural unit B from 2-hydroxyethyl acrylate; The alkenyl ionic liquid is 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS No. 655249-87-9); The lithium salt is calculated as lithium element, and the mass ratio of the structural unit B, the structural unit A, the lithium salt and the solid filler is 1:0.35:0.004:0.065, and the contents of the structural unit B and the structural unit A are calculated as the mass of their corresponding monomers; The lithium salt is lithium bis(trifluoromethanesulfonyl)imide (CAS No. 90076-65-6); The solid filler is selected from a vinyl coupling agent modified molecular sieve; the preparation method of the vinyl coupling agent modified molecular sieve includes: after mixing water and molecular sieve, using ammonia water to adjust the pH value of the system to 9, then adding a vinyl coupling agent to react, filter, and solid-phase dry to obtain a vinyl coupling agent modified molecular sieve; the molecular sieve is selected from ZSM-5 molecular sieve; the average particle size of the ZSM-5 molecular sieve is 120nm, the silicon-aluminum molar ratio is 100, and it is purchased from Shandong Hefa Environmental Protection Technology Co., Ltd.; the volume concentration of ammonia water is 20%; the vinyl coupling agent is coupling agent A-171; the mass ratio of water to molecular sieve is 1:0.43; the mass ratio of vinyl coupling agent to molecular sieve is 1:1.52; the reaction conditions include: temperature of 45°C and time of 1.5 hours; the solid-phase drying conditions include: temperature of 110°C and time of 12h; The three-dimensional foam porous aluminum foil has a thickness of 1.5 mm, a pore size of 5 mm, and a porosity of 50%, and is purchased from Foshan Zhongji Xinmi New Materials Co., Ltd.; the positive electrode active material is NCM622; the positive electrode conductive agent is conductive carbon black; the average particle size of the conductive carbon black is 40 mm, and the model is Super-P-Li (SP); the mass ratio of the positive electrode active material to the positive electrode conductive agent is 100:3.5; The three-dimensional foam porous copper foil has a thickness of 1.5 mm, a pore diameter of 5 mm, and a porosity of 50%, and is purchased from Foshan Zhongji Xinmi New Materials Co., Ltd. The negative electrode active material is selected from lithium titanium oxide (Li4Ti5O 12 ), purchased from Kairui New Materials (Beijing) Technology Co., Ltd.; the negative electrode conductive agent is conductive carbon black; the average particle size of the conductive carbon black is 40 mm, and the model is Super-P-Li (SP); the mass ratio of the negative electrode active material to the negative electrode conductive agent is 100:2.5; The preparation method of the three-dimensional solid-state lithium battery includes: Preparation of S1 positive electrode sheet: The positive electrode active material, positive electrode conductive agent and positive electrode binder were mixed at room temperature for 8 minutes, and then N-methylpyrrolidone was added according to the solid content of 60wt% and mixed for 35 minutes to obtain positive electrode slurry. The positive electrode slurry was then heated to 50mg / cm 2 The surface density weight is coated on a three-dimensional foam porous aluminum foil, passed through a coating machine, and dried in an oven, and finally a positive electrode sheet is punched to obtain a 12 mm circular positive electrode sheet; wherein, the mass ratio of the positive electrode active material to the positive electrode binder is 100:3.5, and the positive electrode binder is a polyvinylidene fluoride binder purchased from Dongguan Fubang Anticorrosion Materials Co., Ltd.; Preparation of S2 negative electrode sheet: The negative electrode active material, negative electrode conductive agent and negative electrode binder were mixed at room temperature for 8 minutes, and then N-methylpyrrolidone was added according to the solid content of 50wt% and mixed for 35 minutes to obtain negative electrode slurry. The negative electrode slurry was then heated to 18mg / cm 2 The surface density weight is coated on the three-dimensional foam porous copper foil, and then the coating machine and oven drying are carried out, and finally the negative electrode sheet is punched to obtain a circular negative electrode sheet with a diameter of 12 mm; wherein, the mass ratio of the negative electrode active material to the negative electrode binder is 100:3.5, and the negative electrode binder is a polyvinylidene fluoride binder purchased from Dongguan Fubang Anticorrosion Materials Co., Ltd.; S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt are mixed at 35°C for 20 minutes, a solid filler is added and mixed for 20 minutes, and an initiator is added and mixed for 8 minutes to obtain a solid electrolyte precursor, the solid electrolyte precursor is cast on a porous rigid support material, initiated at 65°C for 1.5 hours, and polymerized at 50°C for 7 hours, and then punched to obtain a circular diaphragm with a diameter of 12 mm and attached with a solid electrolyte; wherein the organic solvent is selected from ethylene carbonate, the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:0.8, the initiator is dodecyl peroxide, and the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:0.005; the porous rigid support material is selected from a non-woven membrane, the thickness of the non-woven membrane is 300 microns, and it is purchased from Dongguan Kelude New Energy Technology Co., Ltd.; S4 Assembly of three-dimensional solid-state lithium battery: The circular positive electrode sheet in step S1 is attached to one side of the diaphragm with solid electrolyte, and the circular negative electrode sheet in step S2 is attached to the other side of the diaphragm with solid electrolyte, and then heated at 650℃ and 900kg / cm 2 Heat press for 1 minute. Then press at room temperature and 9000kg / cm 2 The battery cell was cold pressed for 3 minutes, and then placed in the shell at 65°C and a pressure of 500kg / cm 2 Heat press for 4 minutes, then press at room temperature and 9000kg / cm 2 A three-dimensional solid-state lithium battery was obtained by cold pressing for 3 minutes.
[0074] Example 2 This embodiment provides a three-dimensional solid-state lithium battery, including a positive electrode sheet, a negative electrode sheet, and a solid electrolyte; the positive electrode sheet includes a three-dimensional foam porous aluminum foil and a positive electrode active material and a positive electrode conductive agent coated on the surface of the three-dimensional foam porous aluminum foil; the negative electrode sheet includes a three-dimensional foam porous copper foil and a negative electrode active material and a negative electrode conductive agent coated on the surface of the three-dimensional foam porous copper foil; the solid electrolyte includes a polymer, a lithium salt, and a solid filler; the polymer contains a structural unit A from an olefinic ionic liquid and a structural unit B from 2-hydroxyethyl acrylate; The alkenyl ionic liquid is 1-allyl-3-butyl imidazole bis(trifluoromethanesulfonyl)imide salt (CAS No. 863498-34-4); The lithium salt is calculated as lithium element, and the mass ratio of the structural unit B, the structural unit A, the lithium salt and the solid filler is 1:0.3:0.003:0.06, and the contents of the structural unit B and the structural unit A are calculated as the mass of their corresponding monomers; The lithium salt is lithium bis(trifluoromethanesulfonyl)imide (CAS No. 90076-65-6); The solid filler is selected from molecular sieves modified by vinyl coupling agents; The preparation method of the vinyl coupling agent modified molecular sieve comprises: after mixing water and molecular sieve, using ammonia water to adjust the pH value of the system to 9-10, then adding the vinyl coupling agent to react, filter, and solid-phase dry to obtain the vinyl coupling agent modified molecular sieve; the molecular sieve is ZSM-5 molecular sieve; the average particle size of the ZSM-5 molecular sieve is 120nm, the silicon-aluminum molar ratio is 100, and it is purchased from Shandong Hefa Environmental Protection Technology Co., Ltd.; the volume concentration of ammonia water is 20%; the vinyl coupling agent is coupling agent A-171; the mass ratio of water to molecular sieve is 1:0.4; the mass ratio of the vinyl coupling agent to the molecular sieve is 1:1.5; the reaction conditions include: temperature of 40°C and time of 2 hours; the solid-phase drying conditions include: temperature of 110°C and time of 12h; The three-dimensional foam porous aluminum foil has a thickness of 1.5 mm, a pore size of 5 mm, and a porosity of 50%, and is purchased from Foshan Zhongji Xinmi New Materials Co., Ltd.; the positive electrode active material is NCM622; the positive electrode conductive agent is conductive carbon black; the average particle size of the conductive carbon black is 40 mm, and the model is Super-P-Li (SP); the mass ratio of the positive electrode active material to the positive electrode conductive agent is 100:3; The three-dimensional foam porous copper foil with a thickness of 1.5 mm, a pore size of 5 mm, and a porosity of 50% was purchased from Foshan Zhongji Xinmi New Materials Co., Ltd.; the negative electrode active material was selected from lithium titanium oxide (Li4Ti5O 12 ), purchased from Kairui New Materials (Beijing) Technology Co., Ltd.; the negative electrode conductive agent is conductive carbon black; the average particle size of the conductive carbon black is 40 mm, and the model is Super-P-Li (SP); the mass ratio of the negative electrode active material to the negative electrode conductive agent is 100:2; The preparation method of the three-dimensional solid-state lithium battery includes: Preparation of S1 positive electrode sheet: The positive electrode active material, positive electrode conductive agent and positive electrode binder were mixed at room temperature for 5 minutes, and then N-methylpyrrolidone was added according to the solid content of 50wt% and mixed for 30 minutes to obtain positive electrode slurry. The positive electrode slurry was then heated to 40mg / cm 2 The surface density weight is coated on a three-dimensional foam porous aluminum foil, passed through a coating machine, and dried in an oven, and finally a positive electrode sheet is punched to obtain a 12 mm circular positive electrode sheet; wherein the mass ratio of the positive electrode active material to the positive electrode binder is 100:3, and the positive electrode binder is a polyvinylidene fluoride binder purchased from Dongguan Fubang Anticorrosion Materials Co., Ltd.; Preparation of S2 negative electrode sheet: The negative electrode active material, negative electrode conductive agent and negative electrode binder were mixed at room temperature for 5 minutes, and then N-methylpyrrolidone was added according to the solid content of 50wt% and mixed for 30 minutes to obtain negative electrode slurry. The negative electrode slurry was then heated to 15mg / cm 2 The surface density weight is coated on the three-dimensional foam porous copper foil, and then the coating machine and oven drying are carried out, and finally the negative electrode sheet is punched to obtain a circular negative electrode sheet with a diameter of 12 mm; wherein, the mass ratio of the negative electrode active material to the negative electrode binder is 100:3, and the negative electrode binder is a polyvinylidene fluoride binder purchased from Dongguan Fubang Anticorrosion Materials Co., Ltd.; S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt are mixed at 30°C for 30 minutes, a solid filler is added and mixed for 30 minutes, and an initiator is added and mixed for 5 minutes to obtain a solid electrolyte precursor, the solid electrolyte precursor is cast on a porous rigid support material, initiated at 60°C for 2 hours, and polymerized at 50°C for 6 hours, and then punched to obtain a circular diaphragm with a diameter of 12 mm and attached with a solid electrolyte; wherein the organic solvent is selected from dimethyl carbonate, the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:0.5, the initiator is dodecyl peroxide, and the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:0.004; the porous rigid support material is selected from a non-woven fabric diaphragm, the thickness of the non-woven fabric diaphragm is 300 microns, and it is purchased from Dongguan Kelude New Energy Technology Co., Ltd.; S4 Assembly of three-dimensional solid-state lithium battery: The circular positive electrode sheet in step S1 is attached to one side of the diaphragm with solid electrolyte, and the circular negative electrode sheet in step S2 is attached to the other side of the diaphragm with solid electrolyte, and then heated at 60°C and 800kg / cm 2 Heat press for 2 minutes. Then press at room temperature and 800kg / cm 2 The battery cell was cold pressed for 4 minutes, and then placed in the shell at 70°C and a pressure of 400 kg / cm 2Heat press for 3 minutes, then at room temperature, 800kg / cm 2 A three-dimensional solid-state lithium battery was obtained by cold pressing for 4 minutes.
[0075] Example 3 This embodiment provides a three-dimensional solid-state lithium battery, including a positive electrode sheet, a negative electrode sheet, and a solid electrolyte; the positive electrode sheet includes a three-dimensional foam porous aluminum foil and a positive electrode active material and a positive electrode conductive agent coated on the surface of the three-dimensional foam porous aluminum foil; the negative electrode sheet includes a three-dimensional foam porous copper foil and a negative electrode active material and a negative electrode conductive agent coated on the surface of the three-dimensional foam porous copper foil; the solid electrolyte includes a polymer, a lithium salt, and a solid filler; the polymer contains a structural unit A from an olefinic ionic liquid and a structural unit B from 2-hydroxyethyl acrylate; The alkenyl ionic liquid is 1-allyl-3-butyl imidazole bis(trifluoromethanesulfonyl)imide salt (CAS No. 863498-34-4); The lithium salt is calculated as lithium element, and the mass ratio of the structural unit B, the structural unit A, the lithium salt and the solid filler is 1:0.4:0.005:0.07, and the contents of the structural unit B and the structural unit A are calculated as the mass of their corresponding monomers; The lithium salt is lithium bis(fluorosulfonyl)imide (CAS No. 171611-11-3); The solid filler is selected from a vinyl coupling agent modified molecular sieve; the preparation method of the vinyl coupling agent modified molecular sieve includes: after mixing water and molecular sieve, using ammonia water to adjust the pH value of the system to 9-10, then adding a vinyl coupling agent to react, filter, and solid-phase dry to obtain a vinyl coupling agent modified molecular sieve; the molecular sieve is selected from ZSM-5 molecular sieve; the average particle size of the ZSM-5 molecular sieve is 120nm, the silicon-aluminum molar ratio is 100, and it is purchased from Shandong Hefa Environmental Protection Technology Co., Ltd.; the volume concentration of ammonia water is 20%; the vinyl coupling agent is coupling agent A-171; the mass ratio of water to molecular sieve is 1:0.5; the mass ratio of vinyl coupling agent to molecular sieve is 1:1.6; the reaction conditions include: temperature of 50°C and time of 1 hour; the solid-phase drying conditions include: temperature of 110°C and time of 12h; The three-dimensional foam porous aluminum foil has a thickness of 1.5 mm, a pore size of 5 mm, and a porosity of 50%, and is purchased from Foshan Zhongji Xinmi New Materials Co., Ltd.; the positive electrode active material is NCM622; the positive electrode conductive agent is conductive carbon black; the average particle size of the conductive carbon black is 40 mm, the model is Super-P-Li (SP), and the mass ratio of the positive electrode active material to the positive electrode conductive agent is 100:4; The three-dimensional foam porous copper foil has a thickness of 1.5 mm, a pore diameter of 5 mm, and a porosity of 50%, and is purchased from Foshan Zhongji Xinmi New Materials Co., Ltd. The negative electrode active material is selected from lithium titanium oxide (Li4Ti5O 12), purchased from Kairui New Materials (Beijing) Technology Co., Ltd.; the negative electrode conductive agent is conductive carbon black; the average particle size of the conductive carbon black is 40 mm, and the model is Super-P-Li (SP); the mass ratio of the negative electrode active material to the negative electrode conductive agent is 100:3; The preparation method of the three-dimensional solid-state lithium battery includes: Preparation of S1 positive electrode sheet: The positive electrode active material, positive electrode conductive agent and positive electrode binder were mixed at room temperature for 10 minutes, and then N-methylpyrrolidone was added according to the solid content of 65wt% and mixed for 40 minutes to obtain positive electrode slurry. The positive electrode slurry was then heated to 60mg / cm 2 The surface density weight is coated on a three-dimensional foam porous aluminum foil, passed through a coating machine, and dried in an oven, and finally a positive electrode sheet is punched to obtain a 12 mm circular positive electrode sheet; wherein, the mass ratio of the positive electrode active material to the positive electrode binder is 100:4, and the positive electrode binder is a polyvinylidene fluoride binder purchased from Dongguan Fubang Anticorrosion Materials Co., Ltd.; Preparation of S2 negative electrode sheet: The negative electrode active material, negative electrode conductive agent and negative electrode binder were mixed at room temperature for 10 minutes, and then N-methylpyrrolidone was added according to the solid content of 65wt% and mixed for 40 minutes to obtain negative electrode slurry. The negative electrode slurry was then heated to 20mg / cm 2 The surface density weight is coated on the three-dimensional foam porous copper foil, and then the coating machine and oven drying are carried out, and finally the negative electrode sheet is punched to obtain a circular negative electrode sheet with a diameter of 12 mm; wherein, the mass ratio of the negative electrode active material to the negative electrode binder is 100:4, and the negative electrode binder is a polyvinylidene fluoride binder purchased from Dongguan Fubang Anticorrosion Materials Co., Ltd.; S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt are mixed at 40°C for 10 minutes, a solid filler is added and the mixture is continued for 10 minutes, and an initiator is added and mixed for 5 minutes to obtain a solid electrolyte precursor, the solid electrolyte precursor is cast on a porous rigid support material, the mixture is initiated at 70°C for 1 hour, and then polymerized at 50°C for 6 hours, and then punched to obtain a circular diaphragm with a diameter of 12 mm and attached with a solid electrolyte; wherein the organic solvent is selected from ethylene carbonate, the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:1, the initiator is dodecyl peroxide, and the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:0.007; the porous rigid support material is selected from a non-woven fabric diaphragm, the thickness of the non-woven fabric diaphragm is 300 microns, and it is purchased from Dongguan Kelude New Energy Technology Co., Ltd.; S4 Assembly of three-dimensional solid-state lithium battery: The circular positive electrode sheet in step S1 is attached to one side of the diaphragm with solid electrolyte, and the circular negative electrode sheet in step S2 is attached to the other side of the diaphragm with solid electrolyte, and then heated at 70°C and 10000kg / cm 2After 1 minute of hot pressing, at room temperature, 10000kg / cm 2 The battery cell was cold pressed for 2 minutes, and then placed in the shell at 80°C and a pressure of 600 kg / cm 2 Heat press for 3 minutes, then press at room temperature and 10000kg / cm 2 A three-dimensional solid-state lithium battery was obtained by cold pressing for 2 minutes.
[0076] Comparative Example 1 The difference between this comparative example and Example 1 is: The polymer contains a structural unit B derived from 2-hydroxyethyl acrylate, the lithium salt is calculated as lithium element, the mass ratio of the structural unit B, the lithium salt and the solid filler is 1:0.004:0.065, and the contents of the structural unit B and the structural unit A are calculated as the mass of their corresponding monomers; S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate and a lithium salt are mixed at 35°C for 20 minutes, a solid filler is added and the mixture is continued for 20 minutes, and an initiator is added and mixed for 8 minutes to obtain a solid electrolyte precursor, the solid electrolyte precursor is cast on a porous rigid support material, initiated at 65°C for 1.5 hours, and polymerized at 50°C for 7 hours, and then punched to obtain a circular diaphragm with a diameter of 12 mm and attached with a solid electrolyte; wherein the organic solvent is selected from ethylene carbonate, and the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:0.8, the initiator is dodecyl peroxide, and the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:0.005; the porous rigid support material is selected from a non-woven fabric diaphragm, and the thickness of the non-woven fabric diaphragm is 300 microns.
[0077] Comparative Example 2 The difference between this comparative example and Example 1 is that the alkenyl ionic liquid is 1-allyl-3-methylimidazolium chloride (CAS No. 65039-10-3).
[0078] Comparative Example 3 The difference between this comparative example and Example 1 is that there is no solid filler, that is, the solid electrolyte includes a polymer and a lithium salt; the lithium salt is calculated as lithium element, and the mass ratio of the structural unit B, the structural unit A and the lithium salt is 1:0.35:0.004; S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt are mixed at 35°C for 20 minutes, and then an initiator is added and mixed for 8 minutes to obtain a solid electrolyte precursor, and the solid electrolyte precursor is cast on a porous rigid support material, initiated at 65°C for 1.5 hours, and then polymerized at 50°C for 7 hours, and then punched to obtain a circular diaphragm with a diameter of 12 mm and attached with a solid electrolyte; wherein the organic solvent is selected from ethylene carbonate, and the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:0.8, the initiator is dodecyl peroxide, and the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:0.005; the porous rigid support material is selected from a non-woven fabric diaphragm, and the thickness of the non-woven fabric diaphragm is 300 microns.
[0079] Comparative Example 4 The difference between this comparative example and Example 1 is that the solid filler is ZSM-5 molecular sieve; the ZSM-5 molecular sieve has an average particle size of 120 nm and a silicon-aluminum molar ratio of 100, and is purchased from Shandong Hefa Environmental Protection Technology Co., Ltd.
[0080] Comparative Example 5 The difference between this comparative example and Example 1 is that the molecular sieve is β molecular sieve, the average particle size of the β molecular sieve is 120 nm, the silicon-aluminum molar ratio is 100, and it is purchased from Shandong Hefa Environmental Protection Technology Co., Ltd.
[0081] Performance Testing 1. Use a LAND charge and discharge instrument to perform constant current charge and discharge tests on the solid-state metal lithium batteries in the above embodiments and comparative examples; Test condition 1 is: the charge cut-off voltage is 4.2V, the discharge cut-off voltage is 2.7V, the charge and discharge test is cycled at a rate of 1C, the test temperature is 25°C, and the specific capacity after the first and 300th cycles of charge and discharge is obtained, and the capacity retention rate is calculated at the same time.
[0082] Test condition 2 is: the charge cut-off voltage is 4.2V, the discharge cut-off voltage is 2.7V, the charge and discharge test is cycled at a rate of 1C, the test temperature is -10°C, and the specific capacity after the first and 300th cycles of charge and discharge is obtained, and the capacity retention rate is calculated at the same time.
[0083] Test condition 3 is: the charge cut-off voltage is 4.2V, the discharge cut-off voltage is 2.7V, the charge and discharge test is cycled at a rate of 1C, the test temperature is 80°C, and the specific capacity after the first and 300th cycles of charge and discharge is obtained, and the capacity retention rate is calculated at the same time.
[0084] 2. The test results are shown in Table 1.
[0085] Table 1 Performance test results
[0086] From the above performance test results, it can be seen that the three-dimensional solid-state lithium batteries in Examples 1-3 have high specific capacity and high-temperature cycle stability and low-temperature cycle stability. It is speculated that this is because the solid electrolyte in the present invention can alleviate the impedance of the positive / negative electrode material and the solid electrolyte interface during the charging and discharging and cycling process of the solid-state lithium battery at room temperature, low temperature and high temperature. In particular, the comprehensive performance of Example 1 is the most outstanding, while the comparative example is significantly worse than the embodiment in the corresponding performance test because it does not adopt the necessary technical scheme. Specifically, in Comparative Example 1, there is no structural unit provided by the ionic liquid in the polymer, and it can be seen that the specific capacity and heat resistance of the solid-state lithium battery are significantly reduced; in Comparative Example 2, other ionic liquids are used as structural fragments in the polymer, and it can be seen that the thermal stability of the solid-state lithium battery is significantly reduced; no solid filler is added to the solid electrolyte in Comparative Example 3, and it can be seen that the specific capacity and low temperature resistance of the solid-state lithium battery are significantly reduced; the solid filler in Comparative Example 4 is not modified with a vinyl coupling agent, and the low temperature resistance and cyclability of the solid-state lithium battery finally obtained are significantly reduced; in Comparative Example 5, a vinyl coupling agent-modified β molecular sieve is used to replace the vinyl coupling agent-modified ZSM-5 molecular sieve, and it can be seen that the specific capacity of the final solid-state lithium battery is reduced to a certain extent. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
[0087] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A three-dimensional solid-state lithium battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte; the positive electrode sheet includes a three-dimensional foam porous aluminum foil and a positive electrode active material and a positive electrode conductive agent coated on the surface of the three-dimensional foam porous aluminum foil; the negative electrode sheet includes a three-dimensional foam porous copper foil and a negative electrode active material and a negative electrode conductive agent coated on the surface of the three-dimensional foam porous copper foil; the solid electrolyte includes a polymer, a lithium salt, and a solid filler; The polymer contains a structural unit A derived from an alkenyl ionic liquid and a structural unit B derived from 2-hydroxyethyl acrylate.
2. The three-dimensional solid-state lithium battery according to claim 1, characterized in that: The alkenyl ionic liquid is selected from at least one of 1-allyl-3-methylimidazolium hexafluorophosphate, 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methylimidazolium trifluoromethanesulfonate, 1-allyl-3-ethylimidazolium hexafluorophosphate and 1-allyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide; the mass ratio of the structural unit B to the structural unit A is 1:(0.1-1).
3. The three-dimensional solid-state lithium battery according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium oxalate borate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate and lithium difluorooxalate borate; and the solid filler is selected from molecular sieves modified by vinyl coupling agents.
4. The three-dimensional solid-state lithium battery according to claim 3, characterized in that: The preparation method of the vinyl coupling agent modified molecular sieve comprises: mixing water and molecular sieve, adjusting the pH value of the system to 9-10 with ammonia water, adding a vinyl coupling agent for reaction, filtering, and solid phase drying to obtain the vinyl coupling agent modified molecular sieve.
5. The three-dimensional solid-state lithium battery according to claim 4, characterized in that: The molecular sieve is selected from ZSM-5 molecular sieve; the average particle size of the ZSM-5 molecular sieve is 20-200nm; the silicon-aluminum molar ratio of the ZSM-5 molecular sieve is 80-100; the vinyl coupling agent is selected from at least one of coupling agent A-171, coupling agent A-151 and coupling agent A-172.
6. The three-dimensional solid-state lithium battery according to claim 4, characterized in that: The mass ratio of water to molecular sieve is 1:(0.3-0.8); the mass ratio of vinyl coupling agent to molecular sieve is 1:(1.2-2); the reaction conditions include: temperature of 40-50°C and time of 1-2 hours; the solid phase drying conditions include: temperature of 100-120°C and time of 8-24 hours.
7. The three-dimensional solid-state lithium battery according to any one of claims 1 to 6, characterized in that: The solid electrolyte is obtained by in-situ polymerization of 2-hydroxyethyl acrylate, alkenyl ionic liquid, lithium salt and solid filler.
8. The three-dimensional solid-state lithium battery according to claim 1, characterized in that: The thickness of the three-dimensional foam porous aluminum foil is 1-2 mm, the pore size is 4-6 mm, and the porosity is 40%-60%; the positive electrode active material is selected from at least one of CM811, NCM622, NCM523 and NCM111; the positive electrode conductive agent is selected from at least one of conductive carbon black, acetylene black, graphene, carbon nanotubes, conductive graphite and carbon fiber; the thickness of the three-dimensional foam porous copper foil is 1-2 mm, the pore size is 4-6 mm, and the porosity is 40%-60%; the negative electrode active material is selected from lithium titanium oxide; the negative electrode conductive agent is selected from at least one of conductive carbon black, graphene and carbon nanotubes; the mass ratio of the negative electrode active material to the negative electrode conductive agent is 100: (2-3).
9. A method for preparing a three-dimensional solid-state lithium battery according to any one of claims 1 to 8, characterized in that: The preparation method comprises: S1 Preparation of positive electrode sheet: The positive electrode active material, positive electrode conductive agent and positive electrode binder are first mixed, and then N-methylpyrrolidone is added according to the solid content of 50-65wt% to continue the second mixing to obtain positive electrode slurry, and then the positive electrode slurry is coated on the three-dimensional foam porous aluminum foil through a coating machine and oven drying, and finally the positive electrode is punched to obtain the positive electrode sheet; S2 Preparation of negative electrode sheet: A negative electrode active material, a negative electrode conductive agent and a negative electrode binder are mixed, and then N-methylpyrrolidone is added according to a solid content of 50-65wt% and mixed to obtain a negative electrode slurry. The negative electrode slurry is then coated on a three-dimensional foam porous copper foil and dried in a coating machine and oven. Finally, a negative electrode sheet is punched to obtain a negative electrode sheet. S3 Preparation of a diaphragm with a solid electrolyte attached: an organic solvent, 2-hydroxyethyl acrylate, an olefinic ionic liquid and a lithium salt are mixed for a third time, a solid filler is added and mixed for 10-30 minutes, and then an initiator is added and mixed for 5-10 minutes to obtain a solid electrolyte precursor, the solid electrolyte precursor is cast on a porous rigid support material to initiate polymerization, and finally punching is performed; S4 Assembly of three-dimensional solid-state lithium battery: attach the positive electrode sheet in step S1 to one side of the diaphragm with solid electrolyte attached, attach the negative electrode sheet in step S2 to the other side of the diaphragm with solid electrolyte attached, and then perform a first pressing to obtain a battery cell, and then place the battery cell into a shell for a second pressing to obtain a three-dimensional solid-state lithium battery.
10. The preparation method according to claim 9, characterized in that: In step S1, the mass ratio of the positive electrode active material to the positive electrode binder is 100:(3-4); the positive electrode binder is selected from polyvinylidene fluoride binder and / or polyacrylate binder; in step S2, the mass ratio of the negative electrode active material to the negative electrode binder is 100:(3-4); the negative electrode binder is selected from polyvinylidene fluoride binder and / or polyacrylate binder; in step S3, the mass ratio of the organic solvent to 2-hydroxyethyl acrylate is 1:(0.5-1); the organic solvent is selected from at least one of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate and dimethyl carbonate; in step S3, the initiator is selected from at least one of dodecyl peroxide, azobisisobutyronitrile, azobisisoheptylonitrile and dimethyl azobisisobutyrate; the mass ratio of the initiator to 2-hydroxyethyl acrylate is 1:(0.004-0.007).
Citation Information
Patent Citations
Multi-layer structured lithium metal electrode and method for manufacturing same
CN106716690A
All-solid battery cell and high-performance all-solid battery containing all-solid battery cell
CN108695558A
Composite positive electrode for solid-state lithium battery and preparation method and application thereof
CN113629221A
Three-dimensional solid-state lithium battery and preparation method thereof
CN112271325A
Polymer electrolyte as well as preparation method and application thereof
CN114400374A
Cited By
Functionalized ionic liquid and preparation method thereof
CN120865096A